343 - Best Practice Guidance on Human Interaction with Technology in Dementia – Recommendations from the INDUCT Network. (October 2020) - Dröes, Rose-Marie; Vermeer, Yvette; Libert, Sébastien; Gaber, Sophie; Wallcook, Sarah; Rai, Harleen; Cavalcanti Barroso, Aline; van Santen, Joeke; Mangiaracina, Floriana; Beentjes, Kim; Bartels, Sara; Christie, Hannah; et al.
Abstract : The Interdisciplinary Network for Dementia Using Current Technology, INDUCT, is a Marie Sklodowska Curie funded International Training Network that aims to develop a multi-disciplinary, inter-sectorial educational research framework for Europe to improve technology and care for people with dementia, and to provide the evidence to show how technology can improve the lives of people with dementia. Within INDUCT (2016-2020) 15 Early Stage Researchers worked on projects in the areas of Technology to support every day life; technology to promote meaningful activities; and health care technology. Three transversal objectives were adopted by INDUCT: 1) To determine the practical, cognitive and social factors needed to make technology more useable for people with dementia; 2) To evaluate the effectiveness of specific contemporary technology; and 3) To trace facilitators and barriers for implementation of technology in dementia care. The main recommendations resulting from the research projects are integrated in a web-based digital Best Practice Guidance on Human Interaction with Technology in Dementia which will be presented at the congress. The recommendations are meant to be helpful for different target groups, i.e. people with dementia, their formal and informal carers, policy makers, designers and researchers, who can easily select the for them relevant recommendations in the Best Practice Guidance by means of a selection tool. The main aim of the Best Practice Guidance is to improve the development, usage and implementation of technology for people with dementia in the three mentioned technology areas. This Best Practice Guidance is the result of the intensive collaborative partnership of INDUCT with academic and non-academic partners as well as the involvement of representatives of the different target groups throughout the INDUCT project. Acknowledgements: The research presented was carried out within the Marie Sklodowska Curie International Training Network (ITN) action, H2020-MSCA-ITN-2015, grant agreement number 676265.